Barrier Systems for Environmental Contaminant Containment and Treatment - Chien, Calvin (CRC Press, 2009)
Containment and permeable reactive barriers have come full circle as an acceptable environmental control technology during the past 30 years. As interest shifted back toward containment in the 1990s, the industry found itself relying largely on pre-1980s technology. Fortunately, in the past 10 years important advances have occurred in several areas of containment, most notably in the area of permeable barriers. A balanced presentation of what is known and not known, Barrier Systems for Contaminant Containment and Environmental Treatment provides a comprehensive report on the current state of the science and technology of waste containment.